7T TOF-MRA shows modulated orifices of lenticulostriate arteries associated with atherosclerotic plaques in patients with lacunar infarcts. Issue 118 (September 2019) - Kong, Qingle; Zhang, Zihao; Yang, Qi; Fan, Zhaoyang; Wang, Bo; An, Jing; Zhuo, Yan
Highlights: The orifices of LSA on MCA can be visualized and analyzed using TOF-MRA at 7 T. Most orifices of LSA are located on the superior and dorsal side of MCA. The ventral and inferior orifices of LSA are mainly affected in patients with LI. The modulated orifices of LSA correlates well with the distribution of plaques. Abstract: Purpose: To characterize the orifices of lenticulostriate arteries (LSAs) in vivo by using three-dimensional (3D) time-of-flight magnetic resonance angiography (TOF-MRA) and to investigate the spatial relationship between LSA orifices and atherosclerotic plaques in patients with lacunar infarcts (LI). Method: Seventeen healthy volunteers and fifteen patients with LI underwent 3D TOF-MRA and 3D vessel wall imaging (VWI) at 7 T. The orifices of LSAs and the locations of atherosclerotic plaques on MCA walls were categorized based on the involvement of the superior, inferior, ventral or dorsal sides of MCA wall. The distribution quadrants of LSA orifices on MCA walls were compared among different groups. Results: Most orifices were located on the superior side of MCA firstly (46 of 95, 48.4%), followed by the dorsal side (22 of 95, 23.2%). In patients with LI, the visible numbers of ventral and inferior orifices on the ipsilateral side were significantly lower than healthy controls ( p = 0.039 for ventral side, p = 0.002 for inferior side). Similarly, plaques occurred more frequently at the ventral (7 of 20, 35.0%) and the inferior (7 of 20, 35.0%) sides of MCA walls. Conclusions: TOF-MRA at 7 T is capable of imaging orifices of LSA on MCA. In patients with LI, the decreased number of LSA orifices on the ventral and inferior sides corresponded with the distribution of MCA plaques. The results may indicate the vulnerability of LSA orifices in intracranial atherosclerosis, which was supposed to be the cause of LI in basal ganglia.